672 Identification of microbial-derived HLA-bound peptides in melanoma. (9th November 2020) - Nagler, Adi; Kalaora, Shelly; Rosenberg, Deborah Gitta; Alon, Michal; Barnea, Eilon; Levy, Ronen; Vervier, Kevin; Trabish, Sophie; Dadosh, Tali; Zaidman, Smadar; Geller, Leore; Greenberg, Polina; et al.
Abstract : Background: The query for tumor shared and neo-antigens as a therapeutic approach has been the focus of cancer immunology for the past two decades. Notably, these peptide sequences can bind to HLA molecules and present on the cell surface, subsequently to be recognized by T-cell receptors (TCRs), activating the immune system and so facilitating in tumor rejection. 1–3 The search for new origins of targetable types of HLA peptides is consistently growing, and new studies show peptides that are derived from non-canonical open reading frames (ORFs), altered translation, proteasome splicing, viral proteins and more. 4–6 In light of the new findings, showing the important role of intra-tumor and gut bacteria in tumor-genesis and their effect on the immune response, 7–10 we went on a quest for discovering whether intracellular bacteria antigens can be presented by tumor cells, and whether these antigens may elicit an immune response. Methods: Combination of HLA peptidomics with 16S rDNA sequencing. Results: Combination of HLA peptidomics with 16S rDNA sequencing of 17 melanoma metastasis derived from 9 different patients, lead us to the unbiased identification of an intracellular bacterial peptide repertoire presented on HLA-I and HLA-II molecules. We were able to validate these results by co-culturing the bacterial species identified by 16S sequencing with the patient derived melanoma cells, further validating the peptide's presentation by preforming HLA peptidomics on the infected cells. Importantly, we were able to identify common bacterial peptides from different metastases of the same patient as well as from different patients. Some of the common bacterial peptides, as well as others, were able to elicit an immune response by the autologous tumor infiltrating lymphocytes (TILs), suggesting potential therapeutic implications of these peptides. Conclusions: The insights gathered through this study elucidate the effect of intra-tumor bacteria on the immune response and so, may lead to the development of novel clinical applications. References: Neefjes J, Jongsma ML, Paul P, Bakke O. Towards a systems understanding of MHC class I and MHC class II antigen presentation. Nat Rev Immunol 2011;11: 823–836. Stronen E, Toebes M, Kelderman S, et al. Targeting of cancer neoantigens with donor-derived T cell receptor repertoires. Science 2016; 352: 1337–1341. Rosenberg SA, Restifo NP. Adoptive cell transfer as personalized immunotherapy for human cancer. Science 2015; 348: 62–68. Chen J, Brunner AD, Cogan JZ, et al. Pervasive functional translation of noncanonical human open reading frames. Science 2020; 367: 1140–1146. Starck SR, Shastri N. Nowhere to hide: unconventional translation yields cryptic peptides for immune surveillance. Immunol Rev 2016;272 :8–16. Croft NP, Smith SA, Pickering J, et al. Most viral peptides displayed by class I MHC on infected cells are immunogenic. Proc Natl Acad Sci U S A 2019; 116: 3112–3117. Gopalakrishnan V, Spencer CN, Nezi L, et al. Gut microbiome modulates response to anti-PD-1 immunotherapy in melanoma patients. Science 2018;359 :97–103. Routy B, Le Chatelier E, Derosa L, et al. Gut microbiome influences efficacy of PD-1-based immunotherapy against epithelial tumors. Science 2018;359 :91–97. Matson V, Fessler J, Bao R, et al. The commensal microbiome is associated with anti-PD-1 efficacy in metastatic melanoma patients. Science 2018;359 :104–108. 10. Nejman D, Livyatan I, Fuks G et al . The human tumor microbiome is composed of tumor type-specific intracellular bacteria. Science 2020;368 :973–980.